KEBIJAKAN STRATEGIS PT. ANEKA TAMBANG TBK: STRATEGIC POLICY OF PT. ANEKA TAMBANG TBK - Ruswana; M. Syamsul Ma’arif; Kirbrandoko (School of Business, Bogor Agricultural University (SB-IPB), 2020)
Ferronickel Production from 2014 to 2018 the highest record was 24,868 Tni or grew 47.5% over the past five years. Alumina Production from 2016 to 2018 has continued to decline. Gold production in the last five years has continued to decline too, While ANTAM's competitors, such as Tsingshan Group for Nickel, Harita Group for Bauxite and Agincort for Gold, showed a performance that exceeded ANTAM. This research was conducted to analyze the strategic policies taken by ANTAM whether they are in accordance with the market situation and the competition map in the mining industry. The research data was obtained through ANTAM's Annual Report and the Annual Report of several other mining companies and other data through the internet media. Strategy Analysis uses 3 stages, stage one to input matrix of the Internal Factor Analysis and External Factor Analysis, stage two matching uses the SWOT Matrix, SPACE Matrix, BCG Matrix, IE Matrix, and GRAND STRATEGY Matrix, as well as stage three selection of strategy using the QSPM matrix. The results showed that the strategy chosen was in accordance with current strategy ANTAM, i.e aggressive, growing, building intensively and integratively through forward integration, backward integration, horizontal integration, product development, market penetration, market development, and related diversification, but in the implementation process it still needed corrections to make adjustments so that the strategy went well. Keywords: SWOT Matrix, SPACE Matrix, BCG Matrix, IE Matrix, QSPM Matrix